Prawo i płeć. Kilka uwag o potencjale krytycznym feministycznej jurysprudencji - Sulikowski, Adam (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2017)
The main purpose of this essay is to examine the critical potential of feminist jurisprudence. Feminist criticism «fits» well into the general assumptions of critical social and legal theory. From the point of view of feminist critique, scientific, social, and juridical discourse are not neutral, but they are determined by different structures of domination. The law is treated by feminist jurisprudence as an element of the social control system and consequently as an instrument of social oppression acting in the interest of groups or structures that have established and governed it. Feminist jurisprudence accepting the unity of dedescription and postulate research and fight addresses many different issues such as the difference between declared and real equality before the law, public / private dichotomy, reproductive rights and access to contraception and abortion, broadly understood education and its impact on the dissemination of stereotypes. In view of the changes that have taken place in Poland after 1989, the critical potential of feminist jurisprudence in the Polish context is considerable.
Keywords: prawoznawstwo feministyczne; teoria krytyczna; feminizm; prawo; równość wobec prawa; edukacja prawnicza; prawa reprodukcyjne